1993
DOI: 10.1007/bf00766158
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of gallium in HZSM5 and HY zeolites by post-synthesis treatment with trimethylgallium

Abstract: Framework gallium was introduced in dealuminated HZSM5 and HY zeolites by treatment with trimethylgallium (TMG). The experiments were successful for both zeolites, particularly when performed in a hydrogen atmosphere. Side reactions of TMG with isolated silanol groups or Bronsted acid sites resulted in the formation of extra-framework gallium. The Ga/HZSM5 zeolite showed an enhanced selectivity to aromatics in the propane conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Bayense et al introduced gallium into H-ZSM-5 and H-Y zeolites by a postsynthesis treatment with trimethylgallium. A problem for the selective introduction of framework gallium into the zeolite structures is the undesired reaction of trimethylgallium with the silanol groups on the outer surface of the zeolite particles.…”
Section: Catalyst Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bayense et al introduced gallium into H-ZSM-5 and H-Y zeolites by a postsynthesis treatment with trimethylgallium. A problem for the selective introduction of framework gallium into the zeolite structures is the undesired reaction of trimethylgallium with the silanol groups on the outer surface of the zeolite particles.…”
Section: Catalyst Formulationsmentioning
confidence: 99%
“…Bayense et al found that highly dispersed gallium in the zeolite (framework or nonframework) possesses dehydrogenation activity.…”
Section: Participation Of Nonframework Gallium Species In the Activat...mentioning
confidence: 99%
“…High dispersion may be achieved by grafting a volatile molecular precursor onto the surface. GaMe 3 has been used in this way to prepare gallosilicate catalysts, in which the resulting Ga sites were assumed to be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Ga/ZSM-5 is the most effective aromatization catalyst, such as the C 3 –C 4 Cyclar process . Various methods including wet impregnation, , isomorphous substitution, , chemical vapor deposition, , and solid-state reaction , have been applied to introduce Ga into the micropores of ZSM-5 . However, segregated Ga 2 O 3 particles at the outer surface of the zeolite crystals were frequently formed, leading to a low Ga dispersion in Ga/ZSM-5 .…”
Section: Introductionmentioning
confidence: 99%